The Function of the MEF2 Family of Transcription Factors in Cardiac Development, Cardiogenomics, and Direct Reprogramming - Desjardins, Cody A. (J Cardiovasc Dev Dis, 2016)
Proper formation of the mammalian heart requires precise spatiotemporal transcriptional regulation of gene programs in cardiomyocytes. Sophisticated regulatory networks have evolved to not only integrate the activities of distinct transcription factors to control tissue-specific gene programs but also, in many instances, to incorporate multiple members within these transcription factor families to ensure accuracy and specificity in the system. Unsurprisingly, perturbations in this elaborate transcriptional circuitry can lead to severe cardiac abnormalities. Myocyte enhancer factor–2 (MEF2) transcription factor belongs to the evolutionarily conserved cardiac gene regulatory network. Given its central role in muscle gene regulation and its evolutionary conservation, MEF2 is considered one of only a few core cardiac transcription factors. In addition to its firmly established role as a differentiation factor, MEF2 regulates wide variety of, sometimes antagonistic, cellular processes such as cell survival and death. Vertebrate genomes encode multiple MEF2 family members thereby expanding the transcriptional potential of this core transcription factor in the heart. This review highlights the requirement of the MEF2 family and their orthologs in cardiac development in diverse animal model systems. Furthermore, we describe the recently characterized role of MEF2 in direct reprogramming and genome-wide cardiomyocyte gene regulation. A thorough understanding of the regulatory functions of the MEF2 family in cardiac development and cardiogenomics is required in order to develop effective therapeutic strategies to repair the diseased heart.